2019
DOI: 10.1111/jns.12344
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors, diagnostic delay, and residual deficits in chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: Management of patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is complicated by the challenging diagnosis, monitoring of disease activity, and treatment response. Real world data about the current practice of care in CIDP are rare, but important to improve clinical guidelines. In this study, we determined the current practice of diagnosis and treatment in relation to the clinical outcome of patients with CIDP in a cross‐sectional study in The Netherlands. All patients registered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…CIDP underdiagnoses, may lead to quite wide-ranging delay in appropriate diagnosis and offering immunotherapeutic treatment as shown in our study, in line with previous studies [3,5]. Moreover, axonal loss in CIDP worsens with time and adversely affects treatment response [22], again prompting the need for early diagnosis and intervention to limit the disability.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…CIDP underdiagnoses, may lead to quite wide-ranging delay in appropriate diagnosis and offering immunotherapeutic treatment as shown in our study, in line with previous studies [3,5]. Moreover, axonal loss in CIDP worsens with time and adversely affects treatment response [22], again prompting the need for early diagnosis and intervention to limit the disability.…”
Section: Discussionsupporting
confidence: 87%
“…We investigated the frequency and causes of pre-referral underdiagnoses of CIDP in consecutive patients attending our specialist inflammatory neuropathy service, and also determined the diagnostic and treatment delay. This aspect of underdiagnoses in treatment responsive CIDP has been explored rarely [3,5]. To the best of our knowledge, this is the first study focussing on specific clinical and electrophysiological features of CIDP contributing In our cohort, 23.3% cases had a pre-referral diagnosis of GBS which was corrected to acute-onset CIDP.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1,2 Despite the published European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) 2010 diagnostic criteria for CIDP, the diagnosis can be challenging, leading to both over-and underdiagnosis. [3][4][5][6][7][8] The extent to which patients can differ in clinical presentation has become more visible in the last decade, resulting in an extended group of atypical CIDP variants, such as distal predominant and asymmetric, for which clear definitions are lacking. 1,9 In addition, not all patients with a clinical suspicion of CIDP completely fulfil the EFNS/PNS 2010 (electro) diagnostic criteria for CIDP.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the ethnical differences and genetic backgrounds between Italy and China may represent reasons for the different rates of disease progression. Finally, several studies have shown that different treatment initiation times and treatment regimens may also lead to different results 26 28 . The uneven distribution of medical resources and limited therapeutic levels in China lead to the late start of treatment for patients, and most patients are treated with hormones; only a few patients have received a single course of IVIg (intravenous immunoglobulin).…”
Section: Discussionmentioning
confidence: 99%